Development of Dynamic Problem-Solving Teaching Method in High School Physics Learning - Abdul Haris; Mutahharah Hasyim; Imam Ramadhan; Nur Aisyah; Fatmawaty Fatmawaty; Teguh Wibawa (Universitas Lambung Mangkurat, 2024)
High-order thinking skills are defined as a process in students that involves applying complex ideas, tends to have multiple possible answers, is open-ended, and involves elaborative thinking. To enhance students' thinking abilities, educators must be creative in creating a learning environment that supports learning objectives. Educators need effective learning strategies and should consider factors that can facilitate students. An ideal learning strategy to develop students' high-order thinking skills focuses on students. The purpose of research on dynamic problem-solving strategies is to understand how learners cope with evolving problems over time or in continuously changing learning environments. One such strategy developed is dynamic problem solving for physics learning. This study tested the feasibility of this method in physics learning using the one-shot case study experimental research method. The research was conducted at SMAN 8 Makassar. The feasibility of the DPS strategy was assessed by four observers, resulting in an average implementation score of 83.19%. Based on these results, the DPS strategy can successfully engage students in physics learning by enhancing their problem-solving skills.